Determination of the parton distribution functions of the proton from ATLAS measurements of differential W± and Z boson production in association with jets - Aad, Georges; Andrei, George Victor; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Krishnan, Anjali; Klassen, Martin; Mkrtchyan, Tigran; Napolitano, Fabrizio; Ott, Philipp; et al. (Journal of high energy physics, 2021)
This article presents a new set of proton parton distribution functions, ATLASepWZVjet20, produced in an analysis at next-to-next-to-leading order in QCD. The new data sets considered are the measurements of W+ and W− boson and Z boson production in association with jets in pp collisions at √8 TeV performed by the ATLAS experiment at the LHC with integrated luminosities of 20.2 fb−1 and 19.9 fb−1, respectively. The analysis also considers the ATLAS measurements of differential W± and Z boson production at √7 TeV with an integrated luminosity of 4.6 fb−1 and deep-inelastic-scattering data from e±p collisions at the HERA accelerator. An improved determination of the sea-quark densities at high Bjorken x is shown, while confirming a strange-quark density similar in size to the up- and down-sea-quark densities in the range x ≲ 0.02 found by previous ATLAS analyses.
Im Titel ist ± hochgestellt
The ATLAS collaboration: G. Aad, V. Andrei, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, F. Napolitano, P.S. Ott, D.F. Rassloff, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 08.03.2022